Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine the equation of a circle given its center and radius, we use the standard form of the equation of a circle:
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
Here, [tex]\((h, k)\)[/tex] represents the coordinates of the center of the circle, and [tex]\(r\)[/tex] represents the radius.
For the given problem:
- The center of the circle is [tex]\((5, -3)\)[/tex]. Thus, [tex]\(h = 5\)[/tex] and [tex]\(k = -3\)[/tex].
- The radius of the circle is 4. Thus, [tex]\(r = 4\)[/tex].
We’ll substitute these values into the standard form equation:
1. Substitute [tex]\(h = 5\)[/tex] and [tex]\(k = -3\)[/tex] into the equation:
[tex]\[ (x - 5)^2 + (y - (-3))^2 = r^2 \][/tex]
2. Simplify the equation where necessary:
[tex]\[ (x - 5)^2 + (y + 3)^2 = r^2 \][/tex]
3. Calculate the value of [tex]\(r^2\)[/tex] (the square of the radius):
[tex]\[ r^2 = 4^2 = 16 \][/tex]
4. Substitute [tex]\(r^2 = 16\)[/tex] into the equation:
[tex]\[ (x - 5)^2 + (y + 3)^2 = 16 \][/tex]
So, the completed equation of the circle is:
[tex]\[ (x - 5)^2 + (y + 3)^2 = 16 \][/tex]
Therefore, the final answer with the blanks filled in is:
[tex]\[ (x - [5])^2 + (y - [-3])^2 = [16] \][/tex]
[tex]\[ (x - h)^2 + (y - k)^2 = r^2 \][/tex]
Here, [tex]\((h, k)\)[/tex] represents the coordinates of the center of the circle, and [tex]\(r\)[/tex] represents the radius.
For the given problem:
- The center of the circle is [tex]\((5, -3)\)[/tex]. Thus, [tex]\(h = 5\)[/tex] and [tex]\(k = -3\)[/tex].
- The radius of the circle is 4. Thus, [tex]\(r = 4\)[/tex].
We’ll substitute these values into the standard form equation:
1. Substitute [tex]\(h = 5\)[/tex] and [tex]\(k = -3\)[/tex] into the equation:
[tex]\[ (x - 5)^2 + (y - (-3))^2 = r^2 \][/tex]
2. Simplify the equation where necessary:
[tex]\[ (x - 5)^2 + (y + 3)^2 = r^2 \][/tex]
3. Calculate the value of [tex]\(r^2\)[/tex] (the square of the radius):
[tex]\[ r^2 = 4^2 = 16 \][/tex]
4. Substitute [tex]\(r^2 = 16\)[/tex] into the equation:
[tex]\[ (x - 5)^2 + (y + 3)^2 = 16 \][/tex]
So, the completed equation of the circle is:
[tex]\[ (x - 5)^2 + (y + 3)^2 = 16 \][/tex]
Therefore, the final answer with the blanks filled in is:
[tex]\[ (x - [5])^2 + (y - [-3])^2 = [16] \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.